Economic and analytical innovations and business models for enterprise management in the modern system of construction development - Krychevs’ka , Yliia (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the study of business models for enterprise management in the modern system of construction development, which is a key factor in ensuring efficiency and competitiveness in a dynamic market environment. The research is based on an analysis of trends in construction, where adaptability, technological innovations, and a focus on long-term project sustainability play a crucial role. Special attention is given to how business models are transforming under the influence of globalization, digitalization, and environmental challenges. The paper examines the main types of business models, including project-oriented models, partnership models, leasing and management models, platform models, and sustainable development models. Particular attention is paid to adapting these models to the specifics of construction projects, integrating innovative technologies, and addressing stakeholder needs. The project-oriented model demonstrates its efficiency in managing the lifecycle of a project, ensuring strategic goals are achieved within budget and time constraints. The partnership model, focused on collaboration between market participants, reduces risks and attracts additional resources, which is critically important for large-scale infrastructure projects. The sustainable development model emphasizes environmental and social aspects, ensuring compliance with modern sustainability requirements. The platform business model is becoming increasingly popular due to the digitalization of the industry, optimizing processes and enhancing productivity through the use of integrated digital platforms. The paper describes the role of such models as platform-based, which ensures project participant integration through digital ecosystems, sustainable development, which focuses on environmental and social responsibility, and hybrid models that combine various approaches to achieve competitive advantages. Based on the analysis of real-world projects, such as "green" buildings and cities of the future, it is shown how digital tools, including BIM and IoT, impact management processes and value creation. The article analyzes the advantages, disadvantages, and practical applications of each model. The findings highlight the need for adapting business models to the conditions of the modern market, integrating innovations, and using sustainable development principles. The proposed conclusions can be useful for researchers, practitioners, and managers in the field of construction development.